Kastom, property and ideology: Land transformations in Melanesia - McDonnell, Siobhan; Allen, Matthew; Filer, Collin (ANU Press, 2017)
The relationship between customary land tenure and 'modern' forms of landed property has been a major political issue in the 'Spearhead' states of Melanesia since the late colonial period, and is even more pressing today, as the region is subject to its own version of what is described in the international literature as a new 'land rush' or 'land grab' in developing countries. This volume aims to test the application of one particular theoretical framework to the Melanesian version of this phenomenon, which is the framework put forward by Derek Hall, Philip Hirsch and Tania Murray Li in their 2011 book, Powers of Exclusion: Land Dilemmas in Southeast Asia. Since that framework emerged from studies of the agrarian transition in Southeast Asia, the key question addressed in this volume is whether 'land transformations' in Melanesia are proceeding in a similar direction, or whether they take a somewhat different form because of the particular nature of Melanesian political economies or social institutions. The contributors to this volume all deal with this question from the point of view of their own direct engagement with different aspects of the land policy process in particular countries. Aside from discussion of the agrarian transition in Melanesia, particular attention is also paid to the growing problem of land access in urban areas and the gendered nature of landed property relations in this region.